PARTISIPASI DAN PENYERAPAN TENAGA KERJA MUSLIMAH DI SEKTOR INFORMAL DALAM MENDUKUNG PERTUMBUHAN EKONOMI YANG BERKELANJUTAN - Dewi Kurniasari; Maolana Efendi (Komitmen: Jurnal Ilmiah Manajemen, 2021)
Although economic growth is increasing continuously, women are more disadvantaged in the labor market than men. While women are underrepresented in the labor force, there are still many of them who are unemployed or not unemployed, who are part-time and informal sector workers, unpaid workers, job-seeking groups, and who are not actively involved in the labor market. In the development of women's empowerment that has occurred so far, the most minor basic problem is women's participation in development, in addition to the existence of various forms of citizenship towards citizenship. One national form is on unpaid work. On average, women spend nineteen percent of their time each day doing unpaid activities, while men only 8 percent. This places a heavy burden on women who have to do paid work and care for paid work. This study aims to examine the participation and absorption of Muslim women workforce in the informal sector in support of sustainable economic growth. This study uses a qualitative approach with descriptive methods in presenting research data as a whole.